Ungendering gendered identities? transgenderism in Malaysia - Michelle Lee Guy (Universiti Kebangsaan Malaysia, 2003)
One of the limitations of gender theories is the lack of emphasis on the phenomenon of gender crossing. While debates on sex and gender surrounding issues of biological and/or social constructions of identity/ies have intended to explain the differences between men and women; transgenderism is highly under-emphasised, if not ignored. This paper intends to explore the pheno-menon of transgenderism in Malaysia by looking at male-to-female transgenderists, popularly known as mak nyah. A few questions are posed and examined, they are: what are the stages of gender crossing? What are the processes and social changes incurred during the transformation? To what extent such transformations affect and are affected by various social aspects? In relation to this, a few essential social institutions are investigated, such as religion, family, tertiary education, peer group, etc. In depth interviews and life stories of transgenderists are utilized to reveal personal perceptions and experiences of gender-crossing and identity reconstruction. These stories also show the strategies of adaptation, seclusion or conversion adopted by transgenderists in reaction to mainstream’s stigmatisation and expectations.